Plato on the Justice of the Individual - Jonescu, Shannon (My University, 1996)
This thesis is an attempt to determine the precise meaning of Plato's notion of justice, as it applies to an individual human being. Specifically, it asks how the Republic's definition of justice as the proper ordering of the parts of a whole must manifest itself in the actual life of a just individual. This amounts to an examination of Plato's conception of the philosophic life. This issue arises, in part, due to a recent trend, exhibited by some of the most influential commentators on Plato, to seek a social, or practical, dimension of philosophic activity. That is, these commentators assume that if Plato's account of the truly just life is to be deemed credible, he must propose, as an essential element of such a life, a course of public and/or political action to be engaged in. Some scholars accuse Plato of failing to meet this criterion of a proper account of the just life, while others try to find evidence to support the claim that Plato did meet it. It is the claim of this thesis that Plato neither did, nor wished to, make 'moral behaviour', as such, an intrinsic part of the philosophic, or just, life. Rather, I argue that Plato is deliberately overturning the ordinary understanding of justice in favour of a conception of the purely contemplative life as the most just. My argument proceeds by way of an analysis of the interpretations of three prominent Plato scholars: David Sachs, Gregory Vlastos, and Terence Irwin. By exposing their misinterpretations of various key passages in Plato's texts, I bring to light the proper interpretation of 'Platonic justice', thus clarifying one of the Republic's central aims, namely to establish exactly why the philosophic life is the best, most just, and happiest life.
Keywords: Justice of the Individual; Plato